2019
DOI: 10.4274/meandros.galenos.2018.86548
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Water Sorption-solubility and Surface Roughness of Different Bulk Fill Composite Resins

Abstract: Objective: This study aimed to investigate and compare the water sorption (WS), solubility (SO) and surface roughness (SR) of four bulk fill resin-based composites (RBCs), a conventional flowable RBC and a conventional hybrid RBC. MaterialsandMethods:Disc-shaped specimens of 3 low-viscosity bulk fill RBCs (SureFil SDR flow, X-tra base, Filtek Bulk Fill flow), 1 high-viscosity bulk fill RBC (Tetric EvoCream Bulk Fill), 1 conventional low-viscosity flowable RBC (Filtek Ultimate flow) and 1 conventional hybrid RB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…They attributed the lower water sorption of bulk-fill RBCs to their higher filler-loading, which increases the filler weight ratio, and in turn requires a smaller polymer matrix. 11 Melo RA et al found that bulk-fill RBC performed better in terms of solubility than conventional. Although the reason for this was not evaluated, the author speculates that the bulk-fill RBC has a higher degree of conversion than the conventional.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They attributed the lower water sorption of bulk-fill RBCs to their higher filler-loading, which increases the filler weight ratio, and in turn requires a smaller polymer matrix. 11 Melo RA et al found that bulk-fill RBC performed better in terms of solubility than conventional. Although the reason for this was not evaluated, the author speculates that the bulk-fill RBC has a higher degree of conversion than the conventional.…”
Section: Discussionmentioning
confidence: 99%
“…10 Earlier studies showed that the type of filler and resin matrix has a significant effect on the solubility of RBCs. [11][12][13] Since chemical structure of bulk-fill is different from conventional RBCs, their solubility in acidic environments may also be different. However, studies on the solubility of bulk-fill RBCs are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Surface properties have great importance on the longevity of resin‐based restorations. A rough surface directly causes biofilm formation, discoloration and gingival irritation, increases the risk of secondary caries, and diminishes restoration gloss (Gonulol et al, 2019). The complex structure of a surface cannot be fully characterized using only surface roughness measurements.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the surface characteristics of the dental materials, profilometry is a common method of quantitative evaluation and is used in many studies (Gonulol, Tunc, Ozer, & Yildizli, 2019; Maden, Altun, Polat, & Basak, 2018; Ruivo, Pacheco, Sebold, & Giannini, 2019). In addition, mechanical properties can be studied, to compare the restorative materials by means of measuring in nanoscale the resistance to permanent indentation.…”
Section: Introductionmentioning
confidence: 99%
“…The specimens (10 mm in diameter and 2 mm in height) were made in a split Teflon mold. 3,6,7 A 1 mm glass Filler content %: 84 (W/w).…”
Section: Specimens Preparationmentioning
confidence: 99%